Dinosaurs and Other Ancient Animals of Big Bend - Collins, Cindi Sirois (University of Texas Press, 2023)
A time-traveling field guide to the ancient version of Big Bend National Park. The sheer beauty of Big Bend National Park, along the shores of the Rio Grande in west Texas, never fails to astonish. Yet what lies beneath this natural treasure may be even more extraordinary than what meets the eye. Hidden in the rocks of Big Bend are the remains of giants: toothy sea lizards, enormous flying reptiles, and dinosaurs. Dinosaurs and Other Ancient Animals of Big Bend is a field guide to what once was. Inspired by the latest research, Cindi Sirois Collins and Asher Elbein imagine what it was like to walk among the plants and animals whose fossil remains tell the story of evolution and geological transformation in this singular landscape. We glimpse the drama of Big Bend's rugged landscape in creation-the desert's emergence from retreating oceans and volcanic eruptions. Immersive vignettes introduce dinosaurs, giant fish, and saber-toothed cats. And the history of discovery in the park proves a gripping tale, as paleontologists sifted major scientific insights from the soils, rocks, and riverbeds. Complete with vivid illustrations, this is a wholly original sensory and narrative experience that will deepen any reader's knowledge and sense of wonder